The Plight of Older Workers Labor Market Experience after Plant Closure in the Swiss Manufacturing Sector - Baumann, Isabel (Life Course Research and Social Policies, 2016)
This open access book examines the economic, social, and psychological consequences of manufacturing plant closure at the individual level. Using an original data set of over 1,200 workers from Switzerland who lost their manufacturing jobs after the financial crisis of 2008, the author analyzes the determinants of reemployment, the sector of reemployment, and the change in wages over a two year period. In addition, coverage also explores how plant closure affects the social relationship between a displaced worker and his or her significant other, which includes a discussion of the coping strategies on the household level as well as how changes in a worker's social and occupational life affects overall satisfaction. Readers will discover that the burden of structural change disproportionately falls on the shoulders of workers aged 55 and older who often face substantial barriers when trying to return to employment. A larger portion of this group experience long-term unemployment and those who do manage to find a new job often suffer disproportionate wage loss. This result is intriguing in the context of the current demographic change and contradicts the common assumption that young and low-qualified individuals are at greatest risk of unemployment. Advanced age-and not low education-appears to be the primary obstacle to workers finding job satisfaction after being laid off because of market conditions. .